A COMPARISON BETWEEN OPTICAL AND RADAR SATELLITE IMAGES FOR DETECTING TROPICAL FOREST FIRES IN SOUTH SUMATRA, INDONESIA - Sunuprapto, Heri; Ali Hussin, Yousif (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2015)
Forest fire in Indonesia is a yearly potential caused for forest degradation. The information available about the main factors that promote the forest fire and information about the forest condition after the forest fire are insufficient . This is one of the reasons why forest area neglected after they are burned. Remote sensing and GIS are helpful tools to provide a quick and accurate data acquisition and that can describe the forest condition after the forest fire. The objectives of this research were to asses the ability of optical and radar satellite remotely sensed data to detect, identify and classify forest damage (burnt area) caused by fire and to develop a spatial model for forest fire hazard. Key words: detection burnt forest, Landsat-TM, ERS, and JERS images